توظيف الوكالة في التورق المصرفي المنظم في البنك الإسلامي RHB : دراسة فقهية تحليلية - Shukriyah Mohamad
Tawarruq is one of the contracts, which is increasingly adopted by Malaysian Islamic Finance Institutions (IFIs) in creating both financing and deposit products. Proper operational execution is needed to ensure its validity so that it will be in line with underlying shari’ah principles. However, as time goes on, the customers of IFIs want all processes involved in each transaction to be simplified by the IFIs as well as minimizing the client’s involvement. From here, IFIs come out with the implementation of the agency (al-wakalah) in tawarruq contracts where at first, it involves three parties namely the client, IFIs, and the broker. However, with the adoption of this agency, only two parties are involved in the trading. Acting on behalf of the client, the IFIs will execute all the transactions. In accordance with this, the jurists differ in the legalization of the agency (al-wakālah) application in tawarruq where some of them allow this application while others do not permit it especially in the application of dual-agencies (al-wakālah al-murakkabah). This triggers jurisprudence (fiqh) issues. The first issue is related to the transfer of ownership (qabḍ) while the second issue is related to the agent who is representing the two parties in a tawarruq contract, one side as an agent and the other in his own capacity. These issues are discussed by assessing Muslim Jurists’ views related to dual-agencies practice. This thesis also adopts the juristic critical analysis method where it analysed the classical and contemporary scholars’ arguments before it emerged with the preferred opinion (tarjih). An interview session with three RHB Islamic Bank’s expert was also conducted on the subject matter to gather the information. First, Head of Shari’ah Advisor at Shari’ah Advisory and Research Department, second Assistant Head of Shari’ah Advisor at Shari’ah Advisory and Management Department and third who is Manager at RHB Islamic Bank located in Ipoh, Perak. This study finally meets its two main findings. First, the issue that said the transfer of ownership does not take place is not relevant because, at RHB Islamic Bank, there is an E-Certificate provided to the customer which reflects the transfer of ownership. Second, RHB Islamic Bank has successfully overcome the problem of an agent who represent two parties in a tawarruq contract where he has obtained an agreement with the customer (muwakkil) about the price of the commodity as well as his own consent to proceed with this transaction.